شیکردنەوەى توانستى خزمەتگوزارییە تەندروستییەکان لە قەزاى پێنجوێن - تالیب, پ.د. جەزا تۆفیق; ڕەشید, هاوژین ئەحمەد (Sulaimani Journal for Humanities, 2023)
Health services are considered one of the oldest basic services because they are related to the health of individuals and society, playing an important role in serving the population within certain limits. Health services are a key factor in development, as there is a strong relationship between health and development measures. Penjwen district is located between the two north latitudes (35◦: 51": 30” – 35◦: 26" : 12”) and the two longitude (46◦: 21:" 06” - 45◦: 46" : 12”) of the east. The aim of this study is to analyze the distribution of health services, present their level of capabilities to the population of the region and estimate the future of services according to population growth. The study also analyzes the capacity of health services and the differences in their distribution. In addition to presenting the obstacles facing the development of this service, the study relies on (descriptive and analytical methods) to identify and analyze the distribution of health services and health services-specific planning measures. As a result of the study, we found that health facilities are not able to provide the most appropriate services to the residents of the district, due to imbalance in the distribution of hospitals, health centers, doctors and health workers in the study area.
Keywords: Services; health; Mean center; Direction of Distribution; Standard Distance and Average Nearest Neighbor